Cultural Soft Power of Korea - Valieva, Julia (Journal of History Culture and Art Research, 2018)
The Republic of Korea plays one of the leading roles in the global economy and is a dynamically developing country. As one of the key elements of South Korea's success, many researchers in their works note the so-called concept of "soft power". The Republic of Korea has great resources of "soft power" and actively uses them. The concept of "soft power" considered in this paper was first proposed by J. Nayem and now this concept has firmly entered the lexicon of world science. The Republic of Korea turned to the concept of "soft power" about twenty years ago. The strategy of the modern concept of "soft power" of the Republic of Korea is based on the dissemination of traditional cultural values and pop culture. South Korea places a great emphasis on the "soft power" of culture, which helped it shape a positive image and create its South Korean attractive brand on the world stage. In this paper, the "soft power" of the culture of South Korea is considered using the example of cybersports and the phenomenon of "Korean wave" or "hullu".